Zambia : Enhanced Initiative for Heavily Indebted Poor Countries-Completion Point Document. (IMF Staff Country Reports; Country Report ;, 2005)
This paper examines Zambia's progress under the Enhanced Initiative for Heavily Indebted Poor Countries. Zambia has met all but three of the completion point conditions, as specified in the decision point document. It made satisfactory progress in implementing and monitoring its Poverty Reduction Strategy Paper for at least one year, and maintained a stable macroeconomic environment as evidenced by satisfactory performance under a program supported by the Poverty Reduction and Growth Facility. Zambia has met the completion point targets in the social sectors, has undertaken important structural reforms, and strengthened public expenditure management.